Therapeutic potentials of Vachellia nilotica (L.) extracts in Hepatitis C infection: A review - Ahovègbé, Lucrèce Y.J.; Ogwang, Patrick E.; Peter, Emanuel L.; Mtewa, Andrew G.; Kasali, Félicien M.; Tolo, Casim U.; Gbenoudon, Judith; Weisheit, Anke; Pakoyo, Kamba F. (My University, 2021)
Hepatitis C Virus (HCV) infection represents a huge burden on healthcare systems world- wide. Vachellia nilotica (V. nilotica) is a widely used plant specie in folk medicine for viral diseases and in some communities for HCV infection. However, little is known regarding its role and possible mechanisms in the prevention and treatment of this viral infection. This review presents ethno-pharmacological, in vitro and in vivo shreds of evidence of the role and underlying mode of action of V. nilotica and its implication in treatment and compli- cation management of HCV infection. PubMed, Library of Congress, SCOPUS, Science Direct and Google scholar databases were searched. Twenty-eight articles of which 15 were in vitro while remaining were in vivo studies were reviewed. V. nilotica’s modes of antiviral activity are direct inactivation of HCV and inhibition of HCV NS3 protease. Its immuno- modulatory activity showed by immune cell proliferation and inhibition of immunosup- pressive cytokine. V. nilotica’s anticancer activity through inhibition of oxidative stress, in- hibition of chromosomal aberrations and enhancement of antioxidant enzymes could be beneficial in treating HCV infection and delaying its progression to cancer. It can be in- ferred that V. nilotica could be a promising source of anti-hepatitis C virus drug leads with the ability to prevent its long-term sequelae while promoting immune competence. Fur- ther studies are needed to explore the applicability of the herb to clinical settings.
Keywords: Vachellia nilotica Hepatitis C; Antiviral; Antioxidant Anti-mutagenic Immuno-modulatory